DAMPAK GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN LOMBOK TIMUR - Athar, Handry Sudiarhta (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- The purpose of this study was to determine the impact of leadership style, organizational commitment, and job satisfaction on employee performance Design/methodology/approach- The type of research is the Assosiative, the location of the research at the Social Service of East Lombok Regency, the sampling technique is accidental sampling based on convenience with a sample of 40 employees. The data used are primary data through questionnaires containing respondents' answers. The collected questionnaires were analyzed by descriptive analysis and then analyzed using the SPSS program. Findings- Descriptive analysis results show that the performance of employees is classified as very high. While the leadership style is high, organizational commitment and job satisfaction are high. The results of testing the research hypothesis show both simultaneously and partially that leadership style, organizational commitment, and job satisfaction significantly influence the performance of East Lombok Regency Social Service employees Implications- Organizations need to increase the effectiveness of leaders through periodic leadership training involving leaders at the middle level. In addition, it is necessary to consider increasing commitment to maintain the sustainable performance of employees Keywords: Performance, Leadership, Organizational Commitment, Job Satisfaction